A new contribution to the Late Quaternary tephrostratigraphy of the Mediterranean: Aegean Sea core LC21. (1st June 2015) - Satow, C.; Tomlinson, E.L.; Grant, K.M.; Albert, P.G.; Smith, V.C.; Manning, C.J.; Ottolini, L.; Wulf, S.; Rohling, E.J.; Lowe, J.J.; Blockley, S.P.E.; Menzies, M.A.
Abstract: Tephra layers preserved in marine sediments can contribute to the reconstruction of volcanic histories and potentially act as stratigraphic isochrons to link together environmental records. Recent developments in the detection of volcanic ash (tephra) at levels where none is macroscopically visible (so-called 'crypto-tephra') have greatly enhanced the potential of tephrostratigraphy for synchronising environmental and archaeological records by expanding the areas over which tephras are found. In this paper, crypto-tephra extraction techniques allow the recovery of 8 non-visible tephra layers to add to the 9 visible layers in a marine sediment core (LC21) from the SE Aegean Sea to form the longest, single core record of volcanic activity in the Aegean Sea. Using a novel, shard-specific methodology, sources of the tephra shards are identified on the basis of their major and trace element single-shard geochemistry, by comparison with geochemical data from proximal Mediterranean volcanic stratigraphies. The results indicate that the tephra layers are derived from 14 or 15 separate eruptions in the last ca 161 ka BP: 9 from Santorini; 2 or 3 from Kos, Yali, or Nisyros; 2 from the Campanian province; and one from Pantelleria. The attributions of these tephra layers indicate that 1) inter-Plinian eruptions from Santorini may have produced regionally significant tephra deposits, 2) marine tephrostratigraphies can provide unique and invaluable data to eruptive histories for island volcanoes, and 3) tephra from both Pantelleria and Campania may be used to correlate marine records from the Aegean Sea to those from the Tyrrhenian, Adriatic and Ionian Seas. Highlights: The first Aegean Sea crypto-tephra investigation. Ash from Campania, Pantelleria, Santorini, Yali and Kos inferred. Major and trace element database provided for glass shards. 14 or 15 separate eruptions represented in one core. Several ash compositions not identified in the proximal volcanic deposits.